Analytical Expression on Characteristic Time Scale of Black Carbon Aging due to Condensation of Hygroscopic Species - Park, Young-Kwon; Park, Sung Hoon; Bae, Gwi-Nam (TAYLOR & FRANCIS INC, 2012)
In this study, the characteristic time scale of black carbon (BC) aging due to condensation of hygroscopic species was parameterized as a function of the condensing species concentration and the size distribution of BC particles. The aging time scale defined based on the BC mass concentration was shown to increase with BC particle size as well as with polydispersity of the size distribution. The effects of the BC particle size distribution on the aging time scale are shown to be considerable in the continuum regime, whereas the aging time scale tends to converge to a constant value in the free-molecule regime. The polydispersity effect was shown to be significant except for extraordinarily small particles. When the aging time scale was defined based on the BC number concentration, the dependency of the aging time scale on polydispersity is much smaller because the effect of slow aging of largest particles is compensated by fast aging of smallest particles. The aging time scale was also shown to be a strong function of the condensing species concentration. The result of this study implies that the aging time scale parameterizations suggested in the previous studies, which did not take into account the effects of condensing species concentration and particle size distribution, cannot be easily generalized for being applied to global model simulations.
Keywords: LIGHT-ABSORPTION; CLOUD MICROPHYSICS; OPTICAL-PROPERTIES; PARTICLE-SIZE; AEROSOL; SOOT; CLIMATE; ATMOSPHERE; MORPHOLOGY; RADIATION